THE IMPACT OF ENDOCRINE PATHOLOGY ON THE OUTCOMES OF IN VITRO FERTILIZATION PROCEDURE - Safarova, A.F. (World of Medicine and Biology, 2024)
The purpose of the study was to find out the influence of endocrine disorders of women on the results of in vitro fertilization procedure. We observed 191 patients undergoing treatment for infertility. Of these, 146 (76.4%) were aged 20–35 years, 45 (23.6%) were aged 36-50 years. The presence and structure of endocrine pathologies and the outcomes of in vitro fertilization were analyzed in the patients. In the structure of somatic diseases in women underwent in vitro fertilization procedure, endocrine pathology predominated: in total 14 of 20 (70 %), 12 (60 %) women had hypothyroidism, 2 (10 %) had type 2 diabetes mellitus. Almost all women with endocrine pathology (12 cases of 14–85.7 %) demonstrated unsuccessful IVF results: a higher IVF failure rate based on absence of transfer was observed in women with hypothyroidism, and based on cycle disruption–in persons with type 2 diabetes mellitus.
Keywords: assisted reproductive technologies; hypothyroidism; diabetes mellitus; pregnancy